122k views
24 votes
Substitute t = 3 and t = 6 to determine if the two expressions are equivalent. 3 (2 t + 5) 6 t + 15 Which statements are true? Select the three correct answers. The value of both expressions when t = 3 is 33. The value of both expressions when t = 3 is 23. The value of both expressions when t = 6 is 41. The value of both expressions when t = 6 is 51. The two expressions are equivalent. The two expressions are not equivalent.

User Klesun
by
5.2k points

2 Answers

5 votes

Answer:

A. The value of both expressions when t=3 is 33

D. The value of both expressions when t = 6 is 51.

E. The two expressions are equivalent.

Explanation:

User Fantouch
by
5.3k points
8 votes

Answer:

If t= 6

3 (2 x 6 + 5) 6 x 6 + 15

3 (12+5) 36 + 15

3 x 17 =51

= 51

The value of both expressio

Explanation:

The value of both expressions when t=6 is 51

When t = 3

3(2 x 3 + 5) 6 x 3 + 15

3 (6 +5) 18 + 15

3 x 11 =33

= 33

The value of both expressions when t= 3 is 33

User Naneri
by
5.9k points